Voices and experiences of health/illness from female victims of gender violence in Tabasco, Mexico. Because this happens to me, I have to suffer - Angela Beatriz Martínez González; Alejandro Arnaldo Barroso Martínez (Social Medicine Publication Group, 2019)
Violence against women has a great impact on health and the health system, they present a greater number of physical and emotional diseases. This phenomenon has been constructed under processes of invisibility and naturalization as a result of a patriarchal society. This work focused on exploring the effects of different forms of violence against women: in terms of health, physical as well as psychological. Under a qualitative methodology, the experience of eight battered women from rural and urban areas of the Mexican state was recovered of Tabasco. To do this, the interview was used through the autobiographical story technique. The findings show that women suffer different types of violence ranging from physical to economic, identified incidence of diseases, suffering and mental suffering caused by violence of any kind. On the other hand, the social constructions about what it means to be a woman in certain circumstances allow to justify the violence exercised by men, in addition in the production of subjectivities of the feminine gender a process of socialization prevails that reduces the woman to her traditional functions and it places it as the sole guarantor of identity.